Reconceptualization and pedagogical strategies of public speaking competency for employability: an integrative review - Zheng, Xiaojian; Mohd Puad, Mohd Hazwan; Ab Jalil, Habibah; Zhendong, Gao; Wei, Wang (Emerald Publishing, 2025)
Purpose – This study investigated the ineffectiveness of public speaking competence (PSC) in fostering employability. By analyzing the competency–training gap, it offers insights into vocational education and training (VET) concerning market-related generic skills. Design/methodology/approach – An integrative review was conducted, qualitatively comparing 23 studies to identify themes, analyze gaps, synthesize recommendations and outline future research directions. Findings – The employability framework of PSC was established, identifying generic skills for vocational diploma students as a developmental priority and graduate attributes for employability (GA-EM) – including career building, self-management and personal traits – as key intervention elements. The role of PSC as a generic skill was clarified through three core components related to GA-EM: (1) self-promotion in job-seeking through public expression, (2) objective self-awareness of disciplinary-specific skill acquisition during speech preparation and (3) mitigating excessive public self-consciousness in job interviews through speech confidence. These findings were re-conceptualized as public speaking competency tailored for employability (PSC-EM), with defined goals, intervention measures and target populations. The PSC-EM developmental gap in VET was refined, and a PSC-training pedagogical framework integrating PSC-EM implementation was proposed. Research limitations/implications – Given the conceptual nature of PSC-EM, VET institutions should corroborate these findings through empirical research. Addressing equity and promoting self-directed learning in PSC training, especially in crowded classrooms in highly populated countries, requires further design-based research. Originality/value – PSC-EM distinguishes PSC from oral communication, assigns it unique generic skill functions and enhances its status in VET. It introduces an innovative approach to employability cultivation, offering both a theoretical framework and a practical guide for VET stakeholders.